Pericles en Lima: el virrey Manso de Velasco, el terremoto y su imagen pública - Barriga Calle, Irma (Pontificia Universidad Católica del Perú, 2022)
This article explores how the Viceroy Count of Superunda built an image of power in the wake of the 1746 earthquake and had painting as a magnificent ally that contributed to consolidate the absolutism of the regime. Faced with the aftermath of the disaster that befell the capital city, he had not only to restore the viceregal power, but also to reestablish the colonial pact, appealing to different converging discourses that would show him as an enlightened ruler and as a protective and magnanimous father. The strong persuasive power of painting played a key role in this.

El artículo explora cómo el virrey conde de Superunda construyó una imagen del poder a raíz del terremoto de 1746 y tuvo en la pintura una magnífica aliada que contribuyó a cimentar el absolutismo del régimen. Ante el desastre que sobrevino en la ciudad capital, debió no solo restaurar el poder virreinal, sino también restablecer el pacto colonial. Para ello, apeló a distintos discursos confluyentes, que lo mostraran como un gobernante ilustrado y como padre protector y magnánimo. En ello, el alto poder persuasivo de la pintura cumplió un rol de primer orden.
Pericles in Lima: the Viceroy Manso de Velasco, the earthquake and his public image
Keywords: Lima; José Antonio Manso de Velasco; Cristóbal Lozano; Earthquake of 1746; Painting; Wheat; Lima; José Antonio Manso de Velasco; Cristóbal Lozano; Terremoto de 1746; Pintura; Trigo; https://purl.org/pe-repo/ocde/ford#6.00.00